Bilateral xanthogranulomatous infammation of nasal and nasopharynx mass : a case report - Boon, Wei Jie; Vong, Khim Soon; Tang, Ing Ping (Egyptian Society of Otolaryngology, 2022)
Background: Xanthogranulomatous infammation is an uncommon condition in adult nasal cavity and nasopharynx. Case presentation: We report a male patient who developed xanthogranulomatous infammation in the bilateral nose and nasopharynx. The patient was not responsive to oral steroid. Multiple biopsies were taken to confrm the defnitive diagnosis, and endoscopic debulking of mass was performed to provide symptomatic relief. Patient was free from nasal symptoms, and residual nasal and nasopharyngeal masses showed no increment in size and number during follow-up. Conclusion: Xanthogranulomatous infammation in the nasal cavity and nasopharynx can be easily confused with other nasal masses. A histopathology examination is crucial to establish the diagnosis. A repeated biopsy is needed if previous biopsy result is inconclusive. Surgical excision is recommended for symptomatic relief. The efectiveness of medical treatment is still unclear. A long-term follow-up is mandatory.